Research and optimisation of focused solar heating system with phase change thermal storage - Zhang, Yishu; Zhang, Wenqing (Frontiers in Energy Research, 2024)
Currently, solar heating systems face several challenges in winter cold conditions, including low heat collection temperature, high heat collection loss, low thermal storage density, and unstable storage temperature, making it difficult to meet heating quality requirements. Taking the heating of a driving school building in the suburbs of Baiyin, Gansu as a case study, and using typical meteorological data for the local heating season, we simulated the indoor thermal load of the building using DEST software. We then designed a focused solar heating system with phase change thermal storage, coupling focused solar thermal technology with latent heat storage technology. The thermal storage performance of Ba(OH)2•8H2O composite phase change material in an oil-sealed environment was verified. Mathematical models of the major components of the focused solar heating system with phase change storage were developed, along with a TRNSYS system model. An objective function was established using the annualized cost method, with the area of the collector and the mass of PCM as variables. Optimization was performed using Genopt software, invoking the Hooke-Jeeves algorithm to optimize the heat collection area S and mass m of phase change material in the focused solar heating system. The optimized results showed a collector area of 4.11 m 2 , and a PCM mass of 130kg, resulting in a 10.04% improvement in the solar assurance rate. Over the system's entire lifecycle, the cost decreased by 1025 RMB, and the carbon emission reduction increased from 10,838kg to 16,101kg.